Drought, warming and soil fertilization effects on leaf volatile terpene concentrations in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Penuelas, Josep; Sardans, Jordi; Llusia, Joan (Acta Physiologiae Plantarum, 2008)
The changes in foliar concentrations of volatile terpenes in response to water stress, fertilization and temperature were analyzed in Pinus halepensis and Quercus ilex. The most abundant terpenes found in both species were a-pinene and D 3 -carene. b-Pinene and myrcene were also abundant in both species. P. halepensis concentrations were much greater than those of Q. ilex in agreement with the lack of storage in the latter species (15205.60 ± 1140.04 vs. 0.54 ± 0.08 lg g -1 [d.m.]). The drought treatment (reduction to 1/3 of full watering) signiﬁcantly increased the total terpene concentrations in both species (54% in P. halepensis and 119% in Q. ilex). The fertilization treatment (addition of either 250 kg N ha -1 or 250 kg P ha -1 or both) had no signiﬁcant effects on terpene foliar concentrations. The terpene concentrations increased from 0.25 lg g -1 [d.m.] at 30C to 0.70 lg g -1 [d.m.] at 40C in Q. ilex (the non-storing species) and from 2,240 lg g -1 [d.m.] at 30C to 15,621 lg g -1 [d.m.] at 40C in P. halepensis (the storing species). Both species presented negative relationship between terpene concentrations and relative water contents (RWC). The results of this study show that higher terpene concentrations can be expected in the warmer and drier conditions predicted for the next decades in the Mediterranean region.
Keywords: fertilization; Pinus halepensis; Quercus ilex; Temperature; terpene concentration; water stress

Drought, warming and soil fertilization effects on leaf volatile terpene concentrations in Pinus halepensis and Quercus ilex (Acta Physiologiae Plantarum, 2008)
The changes in foliar concentrations of volatile terpenes in response to water stress, fertilization and temperature were analyzed in Pinus halepensis and Quercus ilex. The most abundant terpenes found in both species were a-pinene and D 3 -carene. b-Pinene and myrcene were also abundant in both species. P. halepensis concentrations were much greater than those of Q. ilex in agreement with the lack of storage in the latter species (15205.60 ± 1140.04 vs. 0.54 ± 0.08 lg g -1 [d.m.]). The drought treatment (reduction to 1/3 of full watering) signiﬁcantly increased the total terpene concentrations in both species (54% in P. halepensis and 119% in Q. ilex). The fertilization treatment (addition of either 250 kg N ha -1 or 250 kg P ha -1 or both) had no signiﬁcant effects on terpene foliar concentrations. The terpene concentrations increased from 0.25 lg g -1 [d.m.] at 30C to 0.70 lg g -1 [d.m.] at 40C in Q. ilex (the non-storing species) and from 2,240 lg g -1 [d.m.] at 30C to 15,621 lg g -1 [d.m.] at 40C in P. halepensis (the storing species). Both species presented negative relationship between terpene concentrations and relative water contents (RWC). The results of this study show that higher terpene concentrations can be expected in the warmer and drier conditions predicted for the next decades in the Mediterranean region.

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Seasonal emission of monoterpenes by the Mediterranean tree Quercus ilex in field conditions: Relations with photosynthetic rates, temperature and volatility (Physiologia Plantarum, 1999)
The relationships of monoterpene emission with temperature, light, photosynthesis and stomatal conductance (gs) were studied in Quercus ilex L. trees throughout the four annual seasons under field conditions. The highest monoterpene emission was measured in spring and summer (midday average of 11 μg [g DW]−1 h−1), whereas the lowest rates were found in autumn and winter (midday averages of 0.51 and 0.23 μg [g DW]−1 h−1, respectively). In spring and summer, limonene was the monoterpene emitted at highest rate (midday averages of 5.27–6.69 μg [g DW]−1 h−1), whereas α-pinene was emitted the most in autumn and winter (midday averages of 0.31 μg [g DW]−1 h−1). The monoterpenes limonene, α-pinene and β-pinene represented about 75–95% of total detected monoterpenes. The total monoterpene emission rates represented about 0.04% of carbon fixed in autumn, 0.17% in winter, 0.84–2.51% in spring and 1.22–5.13% in summer. Significant correlations of total monoterpene emission with temperature were found when considering either summer emission or the emission over the entire year, whereas significant correlations with net photosynthetic rates were only found when considering summer season. Among individual terpenes, the most volatile, α-pinene and β-pinene, were more correlated with temperature than with net photosynthetic rates whereas the less volatile limonene was more correlated with net photosynthetic rate. Thus, under field conditions it seems that dependency of monoterpene emission on photosynthetic rate or temperature is partly related with volatility of the compounds. Influences of seasonality, temperature, photosynthetic rates and volatility should be considered in inventories and models of emission rates in Mediterranean ecosystems.